Arcuate fasciculus and pre-reading language development in children with prenatal alcohol exposure - Ostertag, Curtis; Reynolds, Jess E.; Kar, Preeti; Dewey, Deborah; Gibbard, W. Ben; Tortorelli, Christina; Lebel, Catherine (Frontiers in Neuroscience, 2023)
Introduction Prenatal alcohol exposure (PAE) contributes to widespread neurodevelopmental challenges, including reading, and has been associated with altered white matter. Here, we aimed to investigate whether arcuate fasciculus (AF) development is associated with pre-reading language skills in young children with PAE. Methods A total of 51 children with confirmed PAE (25 males; 5.6 ± 1.1 years) and 116 unexposed controls (57 males; 4.6 ± 1.2 years) underwent longitudinal diffusion tensor imaging (DTI), for a total of 111 scans from participants with PAE and 381 scans in the unexposed control group. We delineated the left and right AF and extracted mean fractional anisotropy (FA) and mean diffusivity (MD). Pre-reading language ability was assessed using age-standardized phonological processing (PP) and speeded naming (SN) scores of the NEPSY-II. Linear mixed effects models were run to determine the relationship between diffusion metrics and age, group, sex, and age-by-group interactions, with subject modeled as a random factor. A secondary mixed effect model analysis assessed the influence of white matter microstructure and PAE on pre-reading language ability using diffusion metric-by-age-by-group interactions, with 51 age- and sex-matched unexposed controls. Results Phonological processing (PP) and SN scores were significantly lower in the PAE group (p < 0.001). In the right AF, there were significant age-by-group interactions for FA (p < 0.001) and MD (p = 0.0173). In the left AF, there was a nominally significant age-by-group interaction for MD that failed to survive correction (p = 0.0418). For the pre-reading analysis, a significant diffusion-by-age-by-group interaction was found for left FA (p = 0.0029) in predicting SN scores, and for the right FA (p = 0.00691) in predicting PP scores. Discussion Children with PAE showed altered developmental trajectories for the AF, compared with unexposed controls. Children with PAE, regardless of age, showed altered brain-language relationships that resembled those seen in younger typically developing children. Our findings support the contention that altered developmental trajectories in the AF may be associated with functional outcomes in young children with PAE.